DIAGONAL GROWTH CURVE FOR (ZIZIPHUS SPINA CHRISTI) GROWING IN GOVERNORATE ANBAR - Reyam. A. Y. Al-Zaydi; Afak. I. J. Al-Jibouri (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
The research was conducted with the aim of obtaining equations to estimate the diameter growth of different tree ages for the species (Ziziphus spina-christi) to determine the validity of the site for cultivating the species under study. Field data were collected from the site of the University of Anbar in Anbar Governorate, the city of Ramadi. The samples were randomly selected. Cross sections of the tree were taken. The data were collected by conducting the required field measurements, then the data were tabulated using the Excel program, and by using the method of linear and non-linear regression analysis in the Statgraphics2022 statistical program. Obtaining equations for diagonal growth, precision measures were used to compare between equations (coefficient of determination, standard error, and average absolute error). The equation was reached: d = 0.409131 + 1.90377 * A - 0.384178 * P -0.0443618 * T1 for the diameter growth, where the value of the coefficient of determination was (95.98%), the standard error was (0.084), and the mean absolute error was (0.055).